(untitled) - Silbertein, Sandra (New York, 1993)
This book answers both theoretical and practical questions on the teaching of reading. The author offers numerous suggestions on how to teach expository prose, non-prose reading, fiction, poetry and songs, as well as advice on how to help students discern opinion from fact. Textbook examples are complemented with a chapter on how teachers can develop their own materials.
Keywords: English language,Reading; Study and teaching,Foreign speakers